Treatment of Class II Malocclusion With Removable Functional Appliances: A Narrative Review - Hirji, Saima Nizar; Qamruddin, Irfan; Mudassar, Muhammad Adeel; Khurshid, Zohaib; Alam, Mohammad Khursheed (European Journal of General Dentistry, 2021)
Around half of all malocclusions that need orthodontic treatment are Class II in nature. Patients with Class II malocclusion primarily seek treatment for aesthetic improvement. Most of the skeletal class II malocclusions are because of mandibular deficiency, and can be best treated during the growing phase of development by removable functional appliances. The objective of this review is to evaluate and compare skeletal and dentoalveolar effects of various removable functional appliances in the treatment of class II malocclusion. Manual and electronic databases were searched, and out of 5,711 articles, 221 abstracts were shortlisted and reviewed. A total of 19 articles that fulfilled the selection criteria was then retrieved and analyzed. A significant increase in mandibular length and dentoalveolar effects with an increase in vertical dimension in a short time was observed with Twin-Block appliance treatment, followed by Bionator appliance treatment. The long-term stability of results achieved with Twin-Block appliance treatment is still questionable. In addition, Frankel appliance treatment effects are more skeletal in nature, with better control in the vertical dimension. However, it takes a more extended treatment duration to produce similar effects. Based on available evidence, we are convinced that removable functional appliances are valuable tools for correction of the Class II malocclusion at a growing age with a horizontal growth pattern.
Keywords: removable functional appliance; twin block; monoblock appliance; Class II malocclusion and occlusal adjustment